The Effect of Policy Uncertainty on Investment Plans: Evidence from the Unexpected Acceptance of a Far-Reaching Referendum in Switzerland - Klaus Abberger; Andreas Dibiasi; Michael Siegenthaler; Jan-Egbert Sturm (Center for Economic Studies and ifo Institute (CESifo), 2016)
Does increased policy uncertainty dampen investment plans of firms? We provide direct evidence on this question by examining the effects of an unexpectedly accepted and farreaching referendum in Switzerland in February 2014. The vote has put several economically relevant agreements between Switzerland and its main trading partner, the European Union, at stake. Using firm-level survey data levied before and after the vote, we examine whether firms that reported to be affected by the induced policy uncertainty have revised their investment plans differently from those that did not perceive an increase in uncertainty. We find strong evidence that an increase in policy uncertainty does lead firms to reduce their investment plans. As theoretically expected, these effects are concentrated among those firms that view their investments as largely irreversible. Moreover, the uncertainty shock mainly dampened firms' plans to extend their production capacities, while other types of investment such as replacement investment were not affected.
Keywords: D81; D84; E22; 330; investment; uncertainty; irreversibility; business survey